TSLP Exacerbates Septic Inflammation via Murine Double Minute 2 (MDM2) Signaling Pathway - Han, Na-Ra (J Clin Med, 2019)
Thymic stromal lymphopoietin (TSLP) is crucial for Th2-mediated inflammation. Sepsis is a serious systemic inflammatory reaction with organ dysfunction by infection. However, the function of TSLP during sepsis is poorly understood. Thus, we investigated a role and regulatory mechanism of TSLP during sepsis. Sepsis was induced by lipopolysaccharides (LPS) or Escherichia coli DH5α injection in mice. TSLP levels were measured in human subjects, mice, and macrophages. TSLP deficiency or murine double minute 2 (MDM2) deficiency was induced using siRNA or an MDM2 inhibitor, nutlin-3a. We found that TSLP levels were elevated in serum of patients and mice with sepsis. TSLP deficiency lowered liver damage and inflammatory cytokine levels in mice with sepsis. TSLP was produced by the MDM2/NF-κB signaling pathway in LPS-stimulated macrophages. TSLP downregulation by an MDM2 inhibitor, nutlin-3a, alleviated clinical symptoms and septic inflammatory responses. Pharmacological inhibition of TSLP level by cisplatin reduced the septic inflammatory responses. Altogether, the present results show that TSLP exacerbates septic inflammation via the MDM2 signaling pathway, suggesting that TSLP may be a potential target for the treatment of sepsis.